2008
DOI: 10.1097/olq.0b013e31816766af
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of Repeat Dose Terameprocol Vaginal Ointment in Healthy Female Volunteers

Abstract: Terameprocol was well tolerated at a 90 mg dose (2% wt/wt) administered vaginally daily for 7 days. No serious adverse events occurred and any AEs were mild. The excellent safety profile supports future clinical trial to evaluate the application of intravaginal terameprocol in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…This antiviral effect of NDGA is consistent with results obtained for DENV and HCV (9,10). It has to be remarked that the antiviral effects of NDGA or M 4 N also have been observed against viruses from other viral families, such as herpes simplex virus, human immunodeficiency virus, human papillomavirus, cowpox virus, and vaccinia virus (30)(31)(32)(33)(34). Regarding the mechanism behind the antiviral activity of NDGA, in the case of HCV, it was related to an inhibition of the SREBP pathway (10).…”
Section: Discussionsupporting
confidence: 78%
“…This antiviral effect of NDGA is consistent with results obtained for DENV and HCV (9,10). It has to be remarked that the antiviral effects of NDGA or M 4 N also have been observed against viruses from other viral families, such as herpes simplex virus, human immunodeficiency virus, human papillomavirus, cowpox virus, and vaccinia virus (30)(31)(32)(33)(34). Regarding the mechanism behind the antiviral activity of NDGA, in the case of HCV, it was related to an inhibition of the SREBP pathway (10).…”
Section: Discussionsupporting
confidence: 78%
“…These attributes may potentially result in decreased product acceptability. Terameprocol vaginal ointment has been tested for safety and PK in clinical studies [87]. Although encouraging results were obtained, this product was not further investigated because patients preferred a clear hydrogel compared to a white ointment.…”
Section: On-demand Vaginal Rectal and Dual Compartment Dosage Formsmentioning
confidence: 99%
“…These are discussed below in more detail, However, it should be clarified that specific types of dosage forms (as 800 in-situ forming hydrogels) may be initially administered as liquids before 801 they are transformed to semisolids (by increase in their viscosity), due to 802 a specific physiological trigger (as pH or temperature). ointments [173] and were found to be safe and well-tolerated [72,174]. leakage [83], and in another study women reported that the leakage of 865 the product would prevent them from using it again [186].…”
mentioning
confidence: 95%
“…In any case it should be understood that when considering the risk of 172 infection per coitus, the transmission of HIV is relatively infrequent [16], 173 and the risk for infection can be highly affected by the susceptibility of 174 the specific (exposed) individual and by the infectiousness of the specific 175 sexual partner [16]. Genetic studies have recently indicated that in N80% 176 of women infected by the vaginal route, HIV infection is caused by 177 one specific isolate [17-19] (although, this "genetic bottleneck 178 is less pronounced in high-risk individuals" [17] or patients with 179 sexually-transmitted infections [20]).…”
mentioning
confidence: 99%